An Evaluation of Legal Capacity in 18-65 Years Old Population - Aydoğdu, Halil İlhan and Askay, Mehmet and Kırcı, Güven Seçkin and Özer, Erdal (The Bulletin of Legal Medicine, 2017)
Objective: In modern societies, civil law defines specific rights and capacities for individuals. The legal capacity of a person to use those rights encompasses the rights and functions required to be able to acquire responsibilities. When individuals do not have legal capacity for various reasons, the legal system takes the view of those with specialist medical knowledge. To the best of our knowledge, there are no studies in literature which have evaluated the legal capacity of age groups other than geriatrics. Materials and Methods: A retrospective examination was made of the forensic reports of 18-65 years old patients who were referred to the Forensic Medicine Department for evaluation of legal capacity in the period 01/01/2015-31/12/2016. Results: A total of 108 cases were evaluated in the age range of 18-64 years. According to the anamnesis taken, the medical records examined, the tests applied and the psychological status examination, the decisions given were that 56 (51.9%) were restricted in the context of item 405 TMK (Turkish Civil Code), 3 (2.8%) could be restricted on request in the context of item 408 TMK, 11 (10.2%) could be taken into custody in situations determined as threatening him/herself or his/her family with hardship or poverty through extravagance, poor lifestyle and poor management of assets, 4 (3.7%) were defined as eligible for the appointment of a legal advisor and 34 (31.5%) were not determined with any state requiring custody. Conclusion: In this study, it was found that the most common disorder in people between...